Formy pomocy dziecku i rodzinie w strukturach samorządowych - Zieja, Elżbieta (Karkonoska Państwowa Szkoła Wyższa, 2011)
The problem of development of the forms of help being given to a child and family by local governments has been attracting the society's attention in Poland since the beginning of the 1990 s. The analyzed forms of family and child in local communities is only a certain element of the whole care and educational system aimed at achieving European standards. Short statistics of the described reports of the Ministry ofWork and Social Politics and the data of Santa Claus Fund have allowed the author to look into the development of these kinds of help operating in local communities over last decade. Describing the tasks of parish and district councils can differentiate after the legislator the most significant forms of care and support forfamilies in children such as protected flats, specialized family guidance, special centers for families in crisis, day care homes, educational centers, community centers, social and therapeutic centers and clubs.
Keywords: dziecko; rodzina; samorząd gminny; samorząd powiatowy; Ośrodki Interwencji Kryzysowej